Human T cells in silico: Modelling their electrophysiological behaviour in health and disease. (7th September 2016) - Ehling, Petra; Meuth, Patrick; Eichinger, Paul; Herrmann, Alexander M.; Bittner, Stefan; Pawlowski, Matthias; Pankratz, Susann; Herty, Michael; Budde, Thomas; Meuth, Sven G.
Abstract: Although various types of ion channels are known to have an impact on human T cell effector functions, their exact mechanisms of influence are still poorly understood. The patch clamp technique is a well-established method for the investigation of ion channels in neurons and T cells. However, small cell sizes and limited selectivity of pharmacological blockers restrict the value of this experimental approach. Building a realistic T cell computer model therefore can help to overcome these kinds of limitations as well as reduce the overall experimental effort. The computer model introduced here was fed off ion channel parameters from literature and new experimental data. It is capable of simulating the electrophysiological behaviour of resting and activated human CD4 + T cells under basal conditions and during extracellular acidification. The latter allows for the very first time to assess the electrophysiological consequences of tissue acidosis accompanying most forms of inflammation. Highlights: Our model confirms and reproduces the roles of ion currents in immune cell effector function. We collected patch clamp and literature data from ionic currents on CD4+ T cells. Our T cell model predicts electrophysiological behaviour of resting and activated T cells. The model gives insights into changed channel function during tissue inflammation.